An Exploratory Comparison of Ethical Perceptions of Mexican and U.S. Marketers - Marta, Janet (Journal of business ethics, 2008)
This is a study of the effects of a number of background variables on ethical perceptions of Mexican and U.S. marketers. This research investigates how a marketer’s personal religiousness, relativism, and the ethical values influence in perceptions of the degree of ethical problems in hypothetical marketing scenarios. It also examines differences between Mexican and U.S. marketers on these variables. The results show significant differences in perception between the countries, and we discuss the implications of these differences for cross-cultural business activities.